Carrier systems and biosensors for biomedical applications. - Davis, Frank; Higson, Seamus P. J. (Cranfield University, 2007)
This chapter addresses both carrier systems and biosensors which are often applied directly to tissues, either as skin patches, implanted or ingested by a variety of routes. It follows that there is a common theme between these applications and many of those discussed elsewhere within this book. Any device, scaffold or implant within the body must usually display extreme biocompatibility if it is not to cause harm to the patient. The techniques of tailoring surfaces to ensure no adverse reactions are a common theme running throughout this work on tissue engineering.